Provider's Individual and Network Attributes in the Selection Process of a Predominant Antenatal Care Provider in South Carolina: A Case-Control Study - Songyuan Deng; Kevin Bennett (SAGE Publishing, 2024)
Introduction: This study aims to examine the association between provider attributes, including network (patient panel size, degree-number of peer connections, and community size- number of a closely connected group of peers) and individual attributes (travel distance, specialties, and rural practice), and a predominant (most visited) provider. Methods: This study utilized South Carolina's Medicaid claims data during 2014 to 2018, focusing on live births in hospitals. Samples were limited to pregnant women continuously enrolled in Medicaid throughout pregnancy. Predominant providers (total = 2153) were identified for 29 569 pregnancies. Network analyses involved 5520 providers, comprising 3667 antenatal care (ANC) providers and 1853 non-ANC providers. A Cartesian product (n = 45 929 845) combined five annual provider lists with all included pregnancies. Logistic regressions with repeated measures were applied to this retrospective case-control study. Results: The results demonstrated that a medium or large degree were associated with being a predominant provider if the community size was medium or large. A predominant provider was more likely to be located near, rather than far from, the served woman, and in rural areas rather than urban ones. They were also more likely to be specialists, midwives, and nurse practitioners than primary care physicians. Conclusion: The results suggest that both individual and network attributes were significantly associated with being a predominant provider. Policies aimed at addressing access issues for antenatal care should consider both the individual and network attributes of providers, as providers may not be able to alter their individual attributes but can always optimize their social network.